Recurrent anti-TIF1γ-positive dermatomyositis coexisting with postoperative parotid lymphoepithelial carcinoma: a case report with pathogenesis analysis - Cui, Xiaoguang; Ye, Kaihong; Wang, Hong; Kang, Yali; Feng, Junqiao; Wei, Yameng; Xu, Nan; Lei, Fuqian; Wang, Shan; Thorne, Rick F.; Li, Xueyi; La, Ting (Frontiers in Immunology, 2026)
BackgroundAnti-TIF1γ-positive dermatomyositis (DM) is a classic paraneoplastic syndrome in adults, but its coexisting with lymphoepithelial carcinoma (LEC) of the parotid gland is exceptionally rare. This rarity poses significant challenges for clinical management.ObjectiveTo report a unique case of parotid LEC emerging three years after a diagnosis of anti-TIF1γ-positive DM, followed by a post-oncologic DM recurrence. We aimed to investigate the underlying immunopathogenesis through peripheral blood mononuclear cell (PBMC) analysis and genetic profiling.Case presentationA 28-year-old male presented with anti-TIF1γ-positive DM. Three years later, he developed parotid LEC, with Epstein-Barr virus (EBV) detected in both tumor tissue and serology. He was treated with surgical resection and adjuvant therapy, achieving a near-complete oncologic response. However, DM recurred eight months after the cancer diagnosis. Initial cyclophosphamide treatment was effective, but its withdrawal led to relapse; subsequent therapies with methotrexate and tofacitinib provided minimal benefit.ResultsPBMC analysis during the DM recurrence revealed a highly active B-cell population and a reduction in cytotoxic cells. This B-cell expansion subsequently decreased 10 months later, suggesting a delayed effect of the documented EBV activation. Germline genotyping identified a panel of deleterious germline mutations in immune regulation genes, including a variant in CR2 (rs367567954), which encodes a receptor for EBV on B cells and may contribute to their aberrant activation.ConclusionThis case illustrates that refractory anti-TIF1γ-DM can persist even after the associated malignancy is well controlled and underscore the need for long-term vigilance and personalized management strategies in paraneoplastic DM.